2017
DOI: 10.1093/toxsci/kfx038
|View full text |Cite
|
Sign up to set email alerts
|

Epalrestat Stimulated Oxidative Stress, Inflammation, and Fibrogenesis in Mouse Liver

Abstract: Epalrestat (EPS), an aldose reductase inhibitor, is widely prescribed to manage diabetic neuropathy. It is generally believed that EPS is beneficial to diabetic patients because it can protect endothelial cells, Schwann cells, or other neural cells from oxidative stress. However, several clinical studies revealed that EPS therapy led to liver dysfunction, which limited its clinical applications. Currently, the underlying mechanism by which EPS causes liver dysfunction is unknown. This study aimed to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity whereas a very recent study reported that Epalrestat induced oxidative stress, inflammation, and fibrogenesis in the mouse liver [37].…”
mentioning
confidence: 98%
“…Oxidative Medicine and Cellular Longevity whereas a very recent study reported that Epalrestat induced oxidative stress, inflammation, and fibrogenesis in the mouse liver [37].…”
mentioning
confidence: 98%
“…Zopolrestat, an AR-specific inhibitor, improved ethanol-induced steatosis and hepatic oxidative stress by suppressing adenosine monophosphate-activated protein kinase (AMPK) activation and Srebp1c expression in C57BL/6J mice and HepG2 cells [ 99 , 100 ]. Inconsistent with these data, others have reported that epalrestat (EPS), an aldose reductase inhibitor, increased oxidative stress, as indicated by the increased expression of manganese superoxide dismutase (heme oxygenase-1 and NAD(P)H quinone oxidoreductase-1)-induced inflammation, and the infiltration of inflammatory cells and induced the expression of tumor necrosis factor-alpha, CD11b, and CD11c, leading to fibrosis in mouse liver [ 101 ]. Further investigation should be conducted to clarify the relationship between Ar and liver dysfunction.…”
Section: Endogenous Fructose Productionmentioning
confidence: 99%
“…Clinical studies demonstrated the alleviation of spontaneous pain in the lower limbs of 48.6% diabetic patients [ 22 ]. Epalrestat, a carboxylic derivative, has been found beneficial in inhibiting polyol pathway and shielding against nerve damage with no side effects until recently a study conducted by Le et al highlighted the induction of liver fibrogenesis due to increased oxidative stress [ 23 , 24 ]. Studies conducted on tolrestat, zenarestat, and sorbinil suggested their withdrawal from human use because of their adverse effects, i.e., liver dysfunction, increased creatinine levels, and serious hypersensitivity, respectively [ 25 ].…”
Section: Metabolic Pathways Of Painful Diabetic Neuropathy (Pdn) and Potential Therapeutic Agentsmentioning
confidence: 99%